Multidisciplinary Approach to Oral Cancer: The Way to Improve Expectancy and Quality of Life (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The growing improvement of medical sciences in the diagnosis and treatment of head and neck oncological diseases has produced a significant increase in the life expectancy of affected patients. it is therefore necessary to direct new energies towards understanding and protecting the quality of life of cancer patients. This reprint presents the fruit of the research protocols of numerous groups around the world on the topics of life expectancy and quality of life of patients suffering from head and neck cancer.